1991
DOI: 10.1017/s0952523800001322
|View full text |Cite
|
Sign up to set email alerts
|

11-cis retinal restores visual function in vitamin A-deficient Manduca

Abstract: Larvae of the tobacco hornworm moth Manduca sexta were reared on either a carotenoid-supplemented or a carotenoid-deficient diet. The former yields fortified adults with normal visual function, whereas visual sensitivity and rhodopsin content are reduced by 2−4 log units in the compound eyes of the deprived moths reared on the latter. We characterized the retinoids of fortified retinas and investigated the recovery of visual function in deprived moths that were provided with retinaldehyde as a source of photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In Drosophila, opsin is reduced to 1% of normal levels (Ozaki et al, 1993). Visual pigment is restored in mature insect photoreceptors when they are provided with chromophore Bennett & White, 1991;Sapp et al, 1991a;Chen & Stark, 1992). Although the conditions of chromophore depletion and recovery are certainly non-physiological, they provide opportunities for experiments on the possible roles played by the chromophore in regulating synthesis, turnover, maturation and deployment of visual pigment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, opsin is reduced to 1% of normal levels (Ozaki et al, 1993). Visual pigment is restored in mature insect photoreceptors when they are provided with chromophore Bennett & White, 1991;Sapp et al, 1991a;Chen & Stark, 1992). Although the conditions of chromophore depletion and recovery are certainly non-physiological, they provide opportunities for experiments on the possible roles played by the chromophore in regulating synthesis, turnover, maturation and deployment of visual pigment.…”
Section: Discussionmentioning
confidence: 99%
“…Although the conditions of chromophore depletion and recovery are certainly non-physiological, they provide opportunities for experiments on the possible roles played by the chromophore in regulating synthesis, turnover, maturation and deployment of visual pigment. To focus this discussion and avoid the possible complication of species differences, we will consider mainly experiments with Drosophila, but data from the blowfly Calliphora (Paulsen & Schwemer, 1983;Schwemer & Spengler, 1992;Shukolyukov & Denisova, 1992;Huber et at., 1994) and the moth Manduca Bennett & White, 1991) are also relevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some more obviously relevant precursors, especially 1 \-cis retinal, have had limited utility to date because of limited availability. Likewise, ll-cis retinal was applied directly to the head of the moth (Manduca) and led to a small visual recovery (Bennett & White, 1991). Also, many forms of vitamin A do not work well in the diet (Stark, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that eyes of lepidopteran insects are unable to synthesize 3-hydroxyretinoids from retinal or retinol (Vogt 1984;Bennett and White 1991). In order to verify the oxidation of all-trans 3-hydroxyretinol to all-trans 3-hydroxyretinal in the distal layer of the eyes, all-trans retinol was used as a tracer.…”
Section: Oxidation In Vitromentioning
confidence: 99%